Bloom where you're planted - Baham, Darby (Baham, Darby. Friendship chronicles, 2022)
Jennifer Pritchett feels increasingly invisible and left behind as her friends move on to the next steps in their lives. As she goes to therapy to figure out how to bloom in her own right, her boyfriend, Nick Carrington, finds himself being the one left behind. Jennifer wants their relationship to have more intimacy, but he can't help but feel like he's being compared to others--and found wanting. Can they each get what they need out of this relationship? Or will the flowers shrivel up before they do?